The Gay Hussar: The Origins and Spread of Buserant in the Danube Region. (3rd July 2018) - Helmrich, Fabian
ABSTRACT: This papers examines how the word Buserant 'gay' spread in the languages of the Danube region. Further, it hypothesises in what contact situations borrowing occurred. In this, it presents a case study illustrating lexical borrowing in the proposed Danubian Sprachbund . According to the study's findings Italian road workers introduced Buserant in Viennese German from where it spread through army service and/or travellers in taverns of Austria Hungary. The borrowing appears to be restricted to the languages of Austria-Hungary and excludes Yiddish, which can be explained by the relative isolation of Yiddish-speaking communities by the mid-nineteenth century.